Increasing Motivation to Learn English Through The Total Physical Response (TPR) Method: English - Mislawi Yadi; Sirrul Bari; Ach. Fathurrosyid (JOEY: Journal of English Ibrahimy, 2023)
The importance of English in this modern era does not guarantee that students have the motivation to learn English. Most students have low motivation to learn English. It also happened in SMP Ibrahimy 1 Sukorejo. According to the results of the study, the teachers used the lecture method in the learning process. Many students feel bored when learning because the method is less effective. So that many students do not have the motivation to learn English, the researcher used a classroom action research (CAR) approach. CAR consists of three cycles, each cycle consisting of planning, implementation, observation, and reflection. The method used is the Total Physical Response method. The data collection technique used was the Observation Method, Interview Method, Documentation Method, and filling out questionnaires conducted by students. The data analysis technique used was the analysis of increasing motivation through the test again. Based on the learning trials conducted using the total physical response (TPR) method, it was obtained that students' motivation and learning achievement had increased. The increase in motivation to learn English through TPR method was quite large, wherein the Pre-cycle average grade of the class was only 60. In the first cycle 71, the second cycle 81, and the third cycle 92. Seen the results of the N-Gain test recapitulation between pre-cycle and Cycle I, it can be explained that there was an increase in the average N-Gain of 0.27 with low criteria. Furthermore, between cycle, I and cycle II the average increase in N-Gain were 0.31 with moderate criteria, and the last one was the recapitulation of N-Gain test results between cycle II and cycle III of 0.54 with moderate criteria